The Effects of Self-Efficacy and Physical Activity Improving Methods on the Quality of Life in Patients with Diabetes: A Systematic Review - Sajjad Hamidi; Zahra Gholamnezhad; Narges Kasraie; Amirhossein Sahebkar (Journal of Diabetes Research)
Objective. The purpose of this systematic review is to study the impact of self-efficacy-improving strategies on physical activity-related glycemic control of diabetes. Method. This systematic review was conducted based on the PRISMA statement. (“Diabetes” OR “glycemic control”) AND (“exercise” OR “physical activity”) AND “self-efficacy” were searched as keywords in databases including PubMed, Google Scholar, Science Direct, Embase, Cochrane, Web of Science, and Scopus between 2000 and 2019 for relesvant articles. Results. Two reviewers independently screened articles (n=400), and those meeting eligibility criteria (n=47) were selected for data extraction using a predesigned Excel form and critical appraisal using the “Tool for Quantitative Studies.” Different strategies and health promotion programs such as individual or group face-to-face education and multimedia (video conference, video, phone calls, short message service, and Internet-based education) were used in diabetes self-management education programs. The results of different interventions including motivational interviewing (7 studies), exercise (5 studies), multidimensional self-management programs (25 studies), and electronic education (11 studies) had been evaluated. Interventions with more social support, longer duration, combined educative theory-based, and individual education had better outcomes both in postintervention and in follow-up evaluation. Conclusion. A combination of traditional and virtual long-lasting self-care promoting (motivating) programs is needed to improve patients’ self-efficacy for healthy habits like active lifestyle.